DETERMINANTS OF GDP PER CAPITA IN BANGLADESH: AN EMPIRICAL STUDY - Ali, Md. Idris; Faisal-E-Alam, Md. (American Economic & Social Review, 2023)
When making cross-country comparisons regarding the well-being and economic conditions of a population, GDP per capita is the most commonly used indicator. Hence, various economic indicators can affect GDP per capita. This study investigates the impact of inflation, exchange rate, and total reserves (including gold and USD) on GDP per capita in Bangladesh. The study employs a quantitative approach and follows a longitudinal research design. Time series data from 2012 to 2021 is collected using a stratified random sampling technique from the World Development Indicators provided by the World Bank. A range of statistical tests, such as Normality Test, Multivariate Outlier Analysis (Mahalanobis Distance), Multicollinearity Assessment (Tolerance and VIF), Goodness-of-Fit (GoF) Test, ANOVA Test, and Multiple Regression Analysis, were performed using SPSS v.22. The results reveal that exchange rate has a significant influence on GDP per capita, making it crucial factor for economic development, resilience, and export competitiveness. Total reserves were found to have minimal relation with GDP per capita. In contrast, inflation rate, although adversely impacting GDP per capita, remains important for maintaining overall economic stability. Thus, the findings of this study suggest that effective currency management is paramount for economic development. JEL Classification Codes: E31, F31, O47.